Antrojo pasaulinio karo pabėgėlių iš Lietuvos likimą sprendžiant - Pšibilskis, Vygintas Bronius (Lietuvos istorijos studijos, 2000)
During the longest and the most horrible war in the latest history - World War II (1939-1945) - 50 million people were killed and about 40 million were forced into migration and roving about the ruined Europe. Stalinist and Hitlerite occupations of Lithuania, repression, and war ruined the destinies of thousands of people. The greatest part of the political, economic, and cultural elite became refugees and exiles.The Supreme Allied Expeditionary Force took care of the homeless in the beginning. Later, international organizations such as the United Nations Relief and Rehabilitation Administration (UNRRA), International Refugee Organization (IRO), and Intergovernmental Committee on Refugees (IGCR), generously supported by the USA, took over the supervision.In special camps for displaced persons, the exiles had no rights, they suffered shortages, and endured the attempts to send them back to the subjugated country. Even in severe conditions, they did not lose the hope of returning to a free native country. There was active cultural life in the camps, which enhanced the desire to continue seeking knowledge and education.Lithuanian organizations such as the Lithuanian American Council (ALT), United Lithuanian Relief Fund of America (BALF), and Supreme Committee for the Liberation of Lithuania (VLIK) provided invaluable moral and financial support.Overcoming the Soviet Union's intentions to "return Soviet citizens" and standing up against the propagandists of the Soviet regime in America, the destiny of Lithuanian refugees - a specific part of the huge international problem of refugees - was decided during the several years following the war.Having settled in free and democratic countries after emigration, for long decades, the exiles promoted the ideas of Lithuanianism and independence. They protected the values frustrated and despised in the subjugated native land.